Ранньосарматський період у Північному Причорномор’ї - Симоненко, О.В. (Археологія, 1994)
У статті розглядаються історичні та археологічні джере.іа ІІ-І cm до н. е., що пов'язуються з ранньосарматськими племенами, які переселились у цей час на землі колишньої Скіфії. На підставі критичного аналізу повідомлень античних авторів та всебічного розгляду археологічних пам’яток пропонується визначити час появи ранніх сарматів на Україні II cm. до н. е. Аналіз поховального звичаю та матеріальної культури розкриває зв’язки причорноморських пам'яток із східносарматським світом та місцеві особливості, зокрема, орієнтацію у північному секторі. Точки зрения исследователей на время и характер появления сарматов западнее Дона весьма противоречивы: конец IV — начало III в. до н. э. (Д. А. Малинский, Т. Сулимирский, А. Н. Щеглов), вторая половина III в. до н. э. (М. И. Ростовцев, К. Ф. Смирнов, В. И. Костенко) II—I вв. до н. э.(Я. Харматта, М. П. Абрамова, С. В. Полин). Непредвзятый анализ древних текстов свидетельствует, что достоверные сведения о пребывании сарматов в Северном Причерноморье не старше II в. до н. э. («География» Страбона и декрет в честь Диофанта). Археологические источники представлены 61 комплексом (впускные погребения и случайные находки), дата которых также не выходит за пределы ІІ—I вв. до н. э. Некоторые погребения, датированные К. Ф. Смирновым и В. И. Костенко III в. до н. э., отнесены к раннесарматским ошибочно. В раннесарматских погребениях Украины превалирует ориентация в северном секторе. Предлагается идентифицировать их с роксоланами. Немногочисленные погребения с ориентацией в южном секторе по ряду признаков могут быть связаны с языгами. Материальная культура раннесарматских памятников Северного Причерноморья практически не отличается от более восточных регионов (мечи с серповидным навершием, фалары и другие детали конского убора, керамика, украшения). Характерной особенностью причерноморских памятников является широкое распространение фибул среднелатенской схемы, зеркал VI типа (по А. М. Хазанову) и значительная доля античной керамики. Некоторые признаки своеобразных комплексов с налобниками с крючком позволяют поставить вопрос об их сарматской принадлежности. Ареал раннесарматских памятников Северного Причерноморья — Днепро-Донское междуречье. Views of investigators as to the time and type of the Sarmatians’ appearance westwarbs of the Don are rather polar: the end of the 4th and beginning of the 3d cent. B.C. (D. A, Machinsky, T. Sulimirsky, A. N. Shcheglov); the second half of the 3d cent, B.C. (M. I. Rostovtsev, K. F. Smirnov, V. I. Kostenko): the 2nd—1st cent. В. C. (J. Harmatta, M. P. Abramova, S. V. Polin). The unprejudiced analysis of the ancient texts shows that the reliable data about the Sarmatians’ presence at the North Pontic area are dated not earlier than the 2nd cent. E. C. ("Geography" by Strabo and the Diophantes decree). The archaeological sources of this problem include 61 assemblages (introduced graves and findings by chance), date of which does not overstep the limits of the end and 1st cent. B. C. Some graves dated by K. F. Smirnov and V. I. Kostenko the 3d cent. B.C. are attributed to the Early Sarmatian period by mistake. Orientation to the North sector prevails in the Early Sarmatian graves of Ukraine. They are suggested to be identified with Roxolani Rare graves oriented to the South sector may be attributed to Yazyges according to some properties. Material culture of the Early Sarmatian relics of the North Pontic area does not practically differ from it in the East regions (swords with a crescent-shaped pommel, phalerae and other horse-harness, pottery and decoration). Wide spreading of fibulas of the MidLa Tene scheme, mirrors of the 4th type (after A. M. Khazanov) and of antique pottery is a definite peculiarity of the North Pontic relics Central attributes, of original assemblages which include hook-shaped forehead plates permit disputing their Sarmatian belonging. The territory of the Early Sarmatian relics of the North Pontic area embraces the lands between the Don and the Dnieper.